Towards a Fleet of Robots for Orientation, Imaging, and Morphometric Analyses of Planktonic Foraminifera - Knappertsbusch, Michael; Eisenecker, Jean (Frontiers in Marine Science, 2022)
Morphometric shell measurements help to quantify the evolutionary patterns of planktonic foraminifera (marine, calcite-secreting, and floating protists). The study of shell variations of these organisms requires observations at high stratigraphic resolution, which entails morphometric measurements from thousands of specimens. The collection of such data is time-consuming because specimens need to be oriented prior to imaging. In our studies about menardiform, globorotalids through time automatic devices were developed to orientate and image specimens under incident light. A first prototype—Automated Measurement system for shell mORphology (AMOR)—was realized in 2009 and was proven to be advantageous for gathering morphometric data. AMOR consists of a motorized universal tilting stage enabling an automatic orientation of specimens in a multicellular slide under a motorized binocular microscope. After the collection of images from the oriented specimens, shell parameters can be extracted and analyzed using separate digital imaging and morphometric software. AMOR was strongly tuned to Globorotalia menardii, a species with a quasi-symmetrical biconvex geometry in a keel view and often with a non-circular periphery in an equatorial view. Improvements of the software driving AMOR now allow the orientation of spiro- and umbilico-convex profiles and with circular forms in an equatorial view such as in phylogenetically related species like Globorotalia miocenica and Globorotalia multicamerata. Program AMOR v. 3.28 was given more flexibility using a scripting language for automatic control of the Windows graphical user interface. This approach was used to allow combinations of fix orienting functions in AMOR, which released us from reprogramming of the sophisticated LabView code. Scripting of core functions enables developing “portfolios” of adapted recipes for processing the morphologies that are beyond the menardiform morphogroup. To further expand on this concept, a follow-up robot—System AMOR 2—was completed in March 2020. It integrates the modified hardware, a newer digital camera, the updated software (AMOR v. 4.2), and improved functions. The present contribution describes the development from old AMOR to its newer twin, with the perspective of building a fleet of robots for the imaging of the oriented foraminifera in parallel.